Quizlet Transforms Arabic Vocabulary Learning in Education - Agustine, Rilla; Fauji, Imam (Indonesian Journal of Islamic Studies, 2024)
This study explores the development of language vocabulary learning media for "Darsu Lughah Al Arabiyah" using the ADDIE model. With a focus on enhancing Arabic language education, we found a gap in effective vocabulary learning tools. We aimed to develop and evaluate a Quizlet-based vocabulary learning media. Through analysis, design, development, implementation, and evaluation stages, we transitioned from identifying the need for improved methods to implementing a technology-based solution. Results showed positive evaluations from media and material expert validators, with 88% and 96% approval rates, and 81.01% of students responded positively. Our findings suggest Quizlet media's suitability for Arabic vocabulary learning, with implications for future language education practices. Highlight: Enhanced Learning: Quizlet improves Arabic vocabulary acquisition in educational settings. Structured Development: ADDIE model ensures systematic creation and evaluation of materials. Positive Response: Students engage positively, indicating Quizlet's effectiveness in language learning. Keywords: Arabic language education, Vocabulary learning media, ADDIE model, Quizlet, Educational technology